CHRONIC VENOUS INSUFFICIENCY: DEFINITION, PATHOPHYSIOLOGY, DIAGNOSIS, MANAGEMENT, AND PREVENTION - Jakub Nowak; Maksym Sikora; Michał Drabik; Michael Platschek; Klaudia Dybalska; Julia Kosmulska; Mateusz Kęska; Anna Barbara Tuleja; Sylwia Wiktoria Kolano; Karol Józef Szkarłat (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Chronic venous insufficiency (CVI) is a prevalent, progressive condition affecting the lower-limb venous system. It results from venous valve dysfunction, sustained venous hypertension, and chronic inflammation. Despite advances in diagnostic technologies and therapeutic strategies, CVI remains a significant cause of morbidity and decreased quality of life worldwide. Aim: This narrative review aims to provide a comprehensive overview of CVI, highlighting its definition, pathophysiology, clinical presentation, diagnosis, management, and prevention. The review emphasizes evidence-based guidelines and the latest diagnostic and therapeutic technologies, offering an updated perspective on the condition. Methodology: A total of 28 publications were reviewed, consisting of clinical guidelines, systematic reviews, and recent original studies related to CVI. The sources were obtained through PubMed, Scopus, and Cochrane databases, focusing on articles published between 2010 and 2025. Results: CVI typically develops due to venous reflux and microcirculatory dysfunction, leading to symptoms such as edema, skin changes, and ulceration. Duplex ultrasonography is currently the diagnostic gold standard for assessing venous reflux. Advanced imaging techniques, including MR venography, CT venography, infrared thermography, and near-infrared imaging, can improve diagnostic accuracy. Management of CVI involves a multimodal approach, combining compression therapy, pharmacologic treatment, and minimally invasive endovenous techniques. Preventive measures, including weight control, regular physical activity, and consistent use of compression, are crucial to slowing disease progression and reducing the risk of recurrence. Conclusions: CVI remains a significant health and socioeconomic burden globally. Early diagnosis, patient education, and adherence to both conservative and interventional treatments are essential for achieving optimal outcomes. Future directions in CVI management include personalized medicine, digital health integration, and biomarker-driven approaches for earlier detection and targeted therapy.